Some personal traits of children practicing sports in the Syrian Arab Republic - المحيسني عماد المحيسن; معوض وائل مارون; سالمة لؤي (Latakia University Journal -Medical Sciences Series, 2022)
Children who live in the midst of wars, fighting and terrorism, their personality is negatively affected by psychological and social effects such as fear, aggression, subscribing and social integration. Sports activities programs have become a key factor in the formation of the integrated personality of the individual through targeted programs that work to rehabilitate, prepare and treat individuals’ behaviors by exercising The correct sports activities, so recognizing the differences in some personality traits (social integration - aggressiveness - fear - depression) among children according to the variable of the type of sports programs practiced. It is the main objective of this study, using the descriptive approach in a survey style on a sample of (1192) children, where the number of children practicing football programs is (551), basketball (167), handball (55), and volleyball (20). martial games (147), swimming (85), chess (37), athletics (58), and gymnastics (72). The researchers used a resolution for measuring personal traits, and the study concluded that practicing various sports contributes to raise the level of social integration among children, Distinguishing the practitioners of team games and gymnastics in the feature of social integration among children, handball and combat games were distinguished by aggression, gymnastics practitioners were distinguished by the characteristic of fear, practicing various sports reduced depression in children, and athletics practitioners distinguished by depression.